TRAINING EFFECTS ON BODY COMPOSITION AND STRENGTH OF JUNIOR HANDBALL PLAYERS - Cristian FENICI; Bogdan ALMĂJAN-GUȚĂ; Gheorghe MONEA (Cluj University Press, 2022)
Introduction: Coaches and fitness trainers strive through various testing methods to identify appropriate short-term training techniques to achieve the greatest improvements in athletic performance in the shortest possible time. Therefore, studies are needed to evaluate the effects of handball-specific training on selected physical fitness (speed, agility, explosive power, and explosive arm strength) and physiological variables (body fat, body mass, capacity, maximal heart rate, anaerobic endurance) of handball players. The main aim of this study was to develop a complementary strength training program for the development of physical training of professional handball players at junior level, as well as the selection of a test methods to assess fitness. Materials and methods: The research was conducted over a period of 12 months, and during this time a complementary strength training program was applied on an experimental group. The experimental group was represented by 16 junior I athletes from the SCM Politehnica Timișoara handball club, and the control group consisted of 16 junior I athletes from the CSM Resita handball club. The tests aimed the evaluation of the following parameters: body composition and strength before and after training for both groups. Results and discussions: The results obtained show a slight progress of the experimental group in front of the control group in terms of body composition, but an important progress in terms of strength. Conclusions: The study validated that through the modern means of training applied, substantial contributions are made to the increase of sports performance. Received 2022 June 16; Revised 2022 June 30; Accepted 2022 July 8; Available online 2022 June 30; Available print 2022 August 30. REZUMAT. Efectele antrenamentului asupra compoziției corporale și puterii la jucătorii juniori de handbal. Introducere: Antrenorii și preparatorii fizici se străduiesc prin diverse procese de încercare, să identifice tehnici de antrenament adecvate de scurtă durată pentru a obține cele mai mari îmbunătățiri ale per¬formanței sportive într-un timp cât mai scurt. Prin urmare, este nevoie de studii care să evalueze efectele antrenamentului specific handbalului asupra aptitudi¬nilor fizice selectate (viteză, agilitate, putere explozivă, forța explozivă a brațu¬lui) și variabilelor fiziologice (țesutul adipos, masa corporală, capacitatea, ritmul cardiac maxim, anduranța anaerobă) a jucătorilor de handbal masculin. Principalul scop al acestui studiu a fost de a elabora un program de antrenament de forță complementar pentru dezvoltarea pregătirii fizice a handbaliștilor profesioniști la nivel de juniori, precum și selectarea unei baterii de teste pentru evaluarea pregătirii fizice. Materiale și metode: Cercetarea s-a desfășurat pe o perioadă de 12 luni de zile, perioadă în care au fost aplicate mijloacele de antrenament pentru grupa experimentală. Grupa experimentală a fost reprezentată din 16 sportivi juniori I din cadrul clubului de handbal SCM Politehnica Timișoara, iar grupa de control a fost formată din 16 sportivi juniori I din cadrul clubului de handbal CSM Reșița. Prin intermediul testelor s-a urmărit evaluarea următorilor parametrii: compoziția corporală și forța înainte și după antrenament pentru ambele grupuri. Rezultate și discuții: Rezultatele obținute au arătat un ușor progres al grupului experimental comparativ cu grupul de control în ceea ce privește compoziția corporală, dar un progres important în ceea ce privește forța. Studiul a validat că prin mijloacele și moderne de antrenament aplicate, se aduc contribuții substanțiale la creșterea performanțelor sportive. Cuvinte cheie: jucători de handbal juniori, compoziție corporală, antrenament, forță